Oxidative stress and telomere length in COVID-19 patients: Oksidativni status i dužina telomere kod Covid-19 pacijenata - Guzonjic, Azra; Roksandić Milenković, Marina; Dimić, Dejan; Dimić, Nemanja; Timotijević, Ljiljana; Sopić, Miron; Vekić, Jelena; Bogavac-Stanojević, Nataša; Kotur-Stevuljević, Jelena (Archives of Pharmacy, 2022)
The pathogenesis of the COVID-19 infection caused by the SARS-CoV-2 coronavirus is the subject of active research worldwide. As a complex disease, it is suspected that oxidative stress plays a role in its pathogenesis and contributes to the progressive shortening of telomeres. Patients aged 25–84 years (n=31) were monitored at the time of diagnosis, as well as at control on the 14th and 21st days. Redox status parameters were determined: total oxidant status (TOS), superoxide anion radical (O2.-), prooxidant-antioxidant balance (PAB), advanced protein oxidation products (AOPP), malondialdehyde (MDA), and ischemia-modified albumin (IMA) as prooxidants and total antioxidant status (TAS), superoxide-dismutase (SOD) and paraoxonase 1 (PON1) enzyme activity, total antioxidant and total oxidant status ratio (TAS/TOS), and total sulfhydryl groups (SHG) as antioxidants. Patients have the shortest telomeres at diagnosis and their length increases during recovery. A statistically significant difference in rTL was shown in patients at the time of diagnosis and after 21 days (p=0.008). rTL has a statistically significant negative correlation with SHG in patients at the time of diagnosis (ρ=-0.386, p=0.038), as well as in patients after 14 days (ρ =-0.389, p=0.037). After 21 days, a statistically significant positive correlation was shown between rTL and SOD (ρ =0.381, p=0.046). The obtained results indicate progressive shortening of telomeres caused by COVID-19 infection, impaired redox status, as well as the change of these parameters during recovery, which confirms the link between oxidative stress and rTL, as well as the participation of these processes in the pathogenesis of COVID-19.